2021
DOI: 10.1177/09504222211018068
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional teaching of entrepreneurial competences

Abstract: Research on entrepreneurship education (EE) emphasizes the role of learning environments, contexts and pedagogical choices in developing students’ entrepreneurial competences. EE has assumed that it solely carries the task of improving entrepreneurial competences. Yet, the objectives, content and methods of teaching vary, and hence non-entrepreneurship teachers’ classrooms can also provide a learning environment for entrepreneurial competences. However, whether or not this kind of unintentional teaching of ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 86 publications
0
9
0
3
Order By: Relevance
“…EE fosters a positive perception of entrepreneurship and leads to students making a conscious self-assessment of whether they want to pursue an entrepreneurial career or, on the other hand, prefer to employ these newly acquired skills (e.g., creativity, self-confidence, emotional intelligence) in becoming self-employed (Longva et al, 2020). Regardless of this choice, Stenholm et al (2021) point out that students' entrepreneurial capacity is expected to be enhanced by developing entrepreneurial skills in those who are more gifted towards entrepreneurship and clarifying doubts in individuals with less entrepreneurial propensity. Furthermore, Robinson and Stubberud (2014) note that the tools needed to transform ideas into entrepreneurial actions effectively correspond to learning basic skills from management areas such as leading, negotiating, communicating, and working in teams.…”
Section: Entrepreneurial Learningmentioning
confidence: 99%
“…EE fosters a positive perception of entrepreneurship and leads to students making a conscious self-assessment of whether they want to pursue an entrepreneurial career or, on the other hand, prefer to employ these newly acquired skills (e.g., creativity, self-confidence, emotional intelligence) in becoming self-employed (Longva et al, 2020). Regardless of this choice, Stenholm et al (2021) point out that students' entrepreneurial capacity is expected to be enhanced by developing entrepreneurial skills in those who are more gifted towards entrepreneurship and clarifying doubts in individuals with less entrepreneurial propensity. Furthermore, Robinson and Stubberud (2014) note that the tools needed to transform ideas into entrepreneurial actions effectively correspond to learning basic skills from management areas such as leading, negotiating, communicating, and working in teams.…”
Section: Entrepreneurial Learningmentioning
confidence: 99%
“…On the basis of a systematic review, Tittel, and Terzidis (2020) has identified the key entrepreneurial skills: the acquisition and development of resources, collaboration, communication, and the development of business plans, co-operation, coordination, the ability to make decisions, and the development of the organizational culture, empathy, skills, financial skills, ethics, creativity, leadership skills, logical thinking, and monitoring of the activities, skill, planning, problem-solving, etc. the recent Research on entrepreneurship education (Bureau & Komporozos-Athanasiou, 2017;Stenholm et al, 2021) focus on learning environments and contexts that are specifically designed to develop learners ' entrepreneurial skills.…”
Section: Types Of Skills Specific To Adult Learningmentioning
confidence: 99%
“…According to the Organisation for Economic Co-operation and Development's (OECD) publication Developing Entrepreneurship Competencies, entrepreneurship includes creativity, problem-solving skills, initiative, the ability to combine resources, and financial and technological knowledge (OECD, 2018b). There is a core set of entrepreneurship competencies that allow individuals to identify, create and respond to opportunities to create value by pooling resources (Stenholm et al, 2021) and demonstrating self-efficacy, confidence, and a determination to overcome obstacles. These skills can be advanced over time with study and practice (Lans et al, 2014;Tan & Ng, 2006;Gibb & Hannon, 2006;Borjas, 2003;Kirby, 2004).…”
Section: Entrepreneurship and Research Competencementioning
confidence: 99%